Saver Behavior and 401(k) Retirement Wealth - Poterba, James M; Venti, Steven F; Wise, David A (American Economic Review, 2000)
Contributions to 401(k) plans are now the most important form of retirement saving. Since 401(k) plans were introduced in the early 1980’s, they have expanded rapidly and continuously. By 1998, roughly half of all households were eligible to participate in 401(k) plans, and more than 36 million workers made contributions to these employer-provided saving plans. In 1995, the last year for which the U.S. Department of Labor has released definitive data, 401(k) contributions amounted to $87.4 billion, or 55 percent of all contributions to employer-sponsored pension plans. The level of contributions, and their share of all pension contributions, is probably significantly higher today. The spread of 401(k) plans is the most important indicator of the move to personal retirement saving. In 1980, almost 92 percent of pension-plan contributions were to traditional employer-provided plans, and about 64 percent of these contributions were to conventional defined-benefit plans. Today, almost 60 percent of contributions are to personal retirement accounts, including 401(k), IRA, and Keogh plans. Including employerprovided, non-401(k) defined-contribution plans, over 76 percent of contributions are to plans that are controlled in large measure by individuals. These individuals make participation, contribution, asset-allocation, and withdrawal decisions. In this paper, we describe the likely importance of 401(k) assets for future older Americans and the effect of investment decisions on asset accumulation. We also examine the extent to which retirement assets may be affected by several decisions: preretirement withdrawals, management fees and expenses, contribution rates, and early retirement. Our analysis focuses on 401(k) saving, but applies more broadly to other forms of individual retirement saving.